Do we need post-pregnancy screening with human chorionic gonadotrophin after previous hydatidiform mole to identify patients with recurrent gestational trophoblastic disease?. (March 2019) - Earp, K.E.; Hancock, B.W.; Short, D.; Harvey, R.A.; Fisher, R.A.; Drew, D.; Sarwar, N.; Tidy, J.A.; Winter, M.C.; Chien, P.; Seckl, M.J.
Abstract: Objective: To determine whether post-pregnancy human chorionic gonadotrophin screening after previous hydatidiform mole identifies patients with recurrent gestational trophoblastic disease. Study design: A retrospective evaluation of 9315 patients who underwent post-pregnancy screening from 2000 to 2009, as part of the National Gestational Trophoblastic Disease Service in the UK. Results: Patients with previous hydatidiform mole, who had human chorionic gonadotrophin screening after one or more subsequent pregnancies, were identified (n = 9315). Of these, 8630 patients had an initial hydatidiform mole that did not require chemotherapy. In 12, 329 subsequent pregnancy events, screening with human chorionic gonadotrophin identified 3 cases of gestational trophoblastic neoplasm. The remaining 685 patients developed gestational trophoblastic neoplasm, following their initial hydatidiform mole and required chemotherapy. In this group there were 1012 further pregnancy events, human chorionic gonadotrophin screening identified 3 patients with gestational trophoblastic neoplasm. The overall recurrence rate was 6 in 13, 341 events (risk 1: 2227). The rate was 3 in 12, 329 (risk 1:4110) for HM that did not require chemotherapy and 3 in 1012 (1:337) for previously treated gestational trophoblastic neoplasm. All 6 patients with recurrent disease were successfully treated with chemotherapy. Conclusion: Routine post-pregnancy human chorionic gonadotrophin screening may be safely discontinued in patients with one previous uncomplicated hydatidiform mole.